Superior Patency of Upper Arm Arteriovenous Fistulae in High Risk Patients - Chiulli, Larissa C (2011)
BACKGROUND: Despite an increased propensity to primary failure in forearm arteriovenous fistulae compared to upper arm fistulae, forearm fistulae remain the preferred primary access type for chronic hemodialysis patients. In a high risk patient population with multiple medical comorbidities associated with requirement for intravenous access we compared the rates of access failure in forearm and upper arm fistulae. MATERIALS AND METHODS: The records of all patients having primary native arteriovenous fistulae placed between 2004 and 2009 at the VA Connecticut Healthcare system were reviewed (n=118). Primary and secondary patency of upper arm and forearm fistulae were evaluated using Kaplan-Meier survival analysis. The effects of medical comorbidities on access patency were analyzed with Cox regression. RESULTS: The median time to primary failure of the vascular access was 0.288 years in the forearm group compared to 0.940 years in the upper arm group (p=0.028). Secondary patency was 52% at 4.9 years in upper arm fistulae compared to 52% at 1.1 years in the forearm group (p=0.036). There was no significant effect of patient comorbidities on fistula failure; however, there was a trend toward upper arm surgical site as a protective factor for primary fistula patency (Hazard Ratio=0.573, p=0.076). CONCLUSIONS: In veterans needing hemodialysis, a high risk population with extensive comorbid factors often requiring intravascular access, upper arm fistulae are not only a viable option for primary vascular access, but are likely to be a superior option to classic forearm fistulae.